Alpha-radiometry of seawater by liquid scintillation counting - Antoniou, Stella; Costa, Costas; Pashalidis, Ioannis (My University, 2006)
Liquid scintillation counting of the alpha-radionuclides after pre-concentration by cation-exchange represents a simple and robust method for the determination of total alpha-radioactivity in seawater. The total efficiency and the minimum detectable activity were calculated to be 95% and 30 mBq, respectively, for a liter sample and 1000-minute measuring time. The method has been applied successfully for the determination of alpha-radioactivity in seawater from five different coastal areas in Cyprus. The average alpha-radioactivity and uranium concentration were found to be 124±8 mBq·1-1 and 3.2±0.2 μg·1-1, respectively.
Keywords: Alpha radiation; Coastal waters; Ion exchange chromatography; Liquid scintillation counting; Radiation measurement; Radioactive contamination; Radiometry; Sea pollution